Performance Comparison Between Multi-Department OSPF Enterprise Network and Static-Routing Campus Topology (مجلة العلوم الشاملة, 2025)
This research paper presents a comprehensive quantitative comparison between two enterprise network designs: (1) a multi-department topology using the Open Shortest Path First (OSPF) dynamic routing protocol, and (2) an equivalent topology using purely static routing. Both designs connect five organizational departments—Headquarters (HQ), Human Resources (HR), Finance, Sales, and Information Technology (IT)—through serial WAN links and dedicated LAN segments. Performance evaluation is conducted using Quality of Service (QoS) metrics including throughput, end-to-end delay, packet loss, convergence time, scalability, and operational efficiency. Results indicate that while raw forwarding performance (throughput and delay) is nearly identical between both approaches (within ±0.5%), OSPF provides significantly superior advantages in failure recovery, automatic path optimization, and network scalability. OSPF achieves convergence time of 5–10 seconds after topology failures, compared to >60 seconds for manual static route reconfiguration. For networks with more than 10 routers, OSPF's management overhead is reduced by approximately 75% compared to static routing. The analysis demonstrates that although per-packet switching speed is comparable, OSPF-based networks offer critical operational advantages including automatic adaptation to network changes, reduced administrative overhead, faster recovery from failures, and superior scalability to hundreds or thousands of routes. These findings have significant implications for enterprise network design, particularly in organizations requiring high availability, fault tolerance, and ease of management.